India's oral health outlook: challenges, economic impact and need for preventative strategies - Narang, Prashant; Dhoble, Ashok; Mathur, Manu; Rana, Salaj; Mason, Steve; Ali, Asif (Frontiers in Dental Medicine, 2025)
ObjectiveThis review explores the economic and behavioral dimensions of oral health in India, emphasizing the economic burden, treatment-seeking behaviors, and policy-level interventions needed to improve oral health outcomes.MethodsA mixed-method approach was employed, integrating primary data from the Oral Health Observatory (OHO) project (2016–2020) and a systematic review of secondary literature. The OHO project surveyed dental clinic patients using mobile app questionnaires, focusing on oral health behaviors, barriers, and outcomes. Secondary data were analyzed from PubMed, MEDLINE, and Embase databases to assess the economic implications of oral health care in India.ResultsThe OHO data revealed a steady decline in routine dental visits after the age of 35–44 years, while emergency visits persisted across age groups. Gender disparities were observed, with men reporting higher dissatisfaction, greater oral pain, and work disruptions compared to women. Only 44.7% of participants brushed twice daily, and 36.7% brushed before bed. Secondary findings reveal that untreated oral diseases have a higher economic impact than preventive measures. This highlights the need for consumer awareness, strategic policies, and sustainable healthcare frameworks.ConclusionIndia faces significant challenges in oral health due to low awareness, insufficient infrastructure, and economic barriers. Strengthening preventive strategies, increasing public-private partnerships, and integrating oral health education into primary care can dramatically reduce costs and improve population outcomes. A shift from reactive to preventive care is essential for ensuring equitable and sustainable oral health solutions.